Biallelic loss-of-function ZFYVE19 mutations are associated with congenital hepatic fibrosis, sclerosing cholangiopathy and high-GGT cholestasis. Issue 8 (31st July 2020) - Luan, Weisha; Hao, Chen-Zhi; Li, Jia-Qi; Wei, Qing; Gong, Jing-Yu; Qiu, Yi-Ling; Lu, Yi; Shen, Cong-Huan; Xia, Qiang; Xie, Xin-Bao; Zhang, Mei-Hong; Abuduxikuer, Kuerbanjiang; et al.
Abstract : Background: For many children with intrahepatic cholestasis and high-serum gamma-glutamyl transferase (GGT) activity, a genetic aetiology of hepatobiliary disease remains undefined. We sought to identify novel genes mutated in children with idiopathic high-GGT intrahepatic cholestasis, with clinical, histopathological and functional correlations. Methods: We assembled a cohort of 25 children with undiagnosed high-GGT cholestasis and without clinical features of biliary-tract infection or radiological features of choledochal malformation, sclerosing cholangitis or cholelithiasis. Mutations were identified through whole-exome sequencing and targeted Sanger sequencing. We reviewed histopathological findings and assessed phenotypical effects of ZFYVE19 deficiency in cultured cells by immunofluorescence microscopy. Results: Nine Han Chinese children harboured biallelic, predictedly complete loss-of-function pathogenic mutations in ZFYVE19 (c.314C>G, p.S105X; c.379C>T, p.Q127X; c.514C>T, p.R172X; c.547C>T, p.R183X; c.226A>G, p.M76V). All had portal hypertension and, at liver biopsy, histopathological features of the ductal plate malformation (DPM)/congenital hepatic fibrosis (CHF). Four children required liver transplantation for recurrent gastrointestinal haemorrhage. DPM/CHF was confirmed at hepatectomy, with sclerosing small-duct cholangitis. Immunostaining for two primary-cilium axonemal proteins found expression that was deficient intraluminally and ectopic within cholangiocyte cytoplasm. ZFYVE19 depletion in cultured cells yielded abnormalities of centriole and axoneme. Conclusion: Biallelic ZFYVE19 mutations can lead to high-GGT cholestasis and DPM/CHF in vivo. In vitro, they can lead to centriolar and axonemal abnormalities. These observations indicate that mutation in ZFYVE19 results, through as yet undefined mechanisms, in a ciliopathy.